Gold-based lateral-flow strip for the detection of penconazole in watermelon and cucumber samples. (29th January 2022) - Liu, Yang; Xu, Xinxin; Liu, Liqiang; Xu, Liguang; Kuang, Hua; Xu, Chuanlai
Abstract: As a typical triazole fungicide, penconazole (PEN) is widely used in agriculture but has been proven to be toxic. In this study, we designed a new hapten to prepare a highly sensitive and specific anti-PEN monoclonal antibody (mAb) and established a gold nanoparticle-based lateral-flow immunoassay (LFIA) for the detection of PEN residues in watermelon and cucumber. The 50% inhibitory concentration (IC50 ) of the mAb was 0.42 ng/mL and the LFIA strip had a visual limit of detection (vLOD) of 2.5 ng/g and a cut-off value of 10 ng/g in watermelon and cucumbers. The calculated limit of detection (LOD) of the LFIA strip was 0.36 ng/g for watermelon and 0.29 ng/g for cucumber. The LFIA strip also gave a recovery rate of 92.5%–109.0% for watermelon samples and 92.5%–106.7% for cucumber samples. These results using the LFIA strip are highly consistent with those seen using liquid chromatography–tandem mass spectrometry. Thus our developed LFIA strip represents a potentially reliable tool for the rapid on-site screening for PEN in watermelons and cucumbers.